Activities of the National Association of Specialists for the Control of Healthcare-Associated Infections - N. I. Briko; O. V. Kovalishena; R. V. Polibin (Эпидемиология и вакцинопрофилактика, 2017)
The article presents the results of the activities of the National Association of Specialists for the Control of Healthcare -Associated Infections of ensuring epidemiological safety of medical care. Educational projects, development and the statement of federal clinical guidelines, participation in development of criteria of an assessment of epidemiological safety and audit of the healthcare settings for system of ensuring quality and safety of medical care are discussed. Priority tasks to safety of patients and the medical staff, assistance in improving immunization programs and the National Schedule of preventive vaccinations, transition to new risk-to the focused strategy of an epidemiological surveillance and prevention of infections in the healthcare settings are defined.